2018
DOI: 10.1128/aac.00239-18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the In Vivo Activity of SPR741 in Combination with Azithromycin against Multidrug-Resistant Enterobacteriaceae Isolates in the Neutropenic Murine Thigh Infection Model

Abstract: SPR741 is a novel agent with structural similarity to polymyxins that is capable of potentiating the activities of various classes of antibiotics. Previously published studies indicated that although isolates had minimal susceptibilities to azithromycin (AZM), the antimicrobial activity of AZM against was enhanced when it was combined with SPR741. The current study evaluated the activity of human-simulated regimens (HSR) of AZM equivalent to clinical doses of 500 mg given intravenously (i.v.) every 24 h (q24h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…The rise of antibiotic resistance in Gram-negative pathogens has brought renewed attention to this area. Indeed, a wealth of recent work shows that OM perturbants in combination with traditionally Gram-positive active antibiotics can successfully treat murine infection models of Acinetobacter baumannii ( 10 , 21 ), Klebsiella pneumoniae ( 22 ), and Escherichia coli ( 23 ). In 2017, the first OM perturbant SPR741, a derivative of PMBN ( 24 ), completed phase Ia and Ib clinical trials with a promising pharmacokinetic and tolerability profile ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rise of antibiotic resistance in Gram-negative pathogens has brought renewed attention to this area. Indeed, a wealth of recent work shows that OM perturbants in combination with traditionally Gram-positive active antibiotics can successfully treat murine infection models of Acinetobacter baumannii ( 10 , 21 ), Klebsiella pneumoniae ( 22 ), and Escherichia coli ( 23 ). In 2017, the first OM perturbant SPR741, a derivative of PMBN ( 24 ), completed phase Ia and Ib clinical trials with a promising pharmacokinetic and tolerability profile ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Analogs of polymyxin tested in this study have been synthesized with shorter peptide chains (as observed for the deacylated polymyxin B nonapeptide [PMBN]), modified acyl chains, and substituted amino acid residues ( Fig. 1) (10)(11)(12)(13). These modifications were made to reduce nephrotoxicity and allow for treatment at more effective concentrations.…”
mentioning
confidence: 99%
“…Therefore, researchers have attempted to develop derivatives of polymyxin to improve its properties. Analogs of polymyxin, SPR741, SPR1205, SPR206, and SPR946 have been designed by shortening the peptide chains, by modifying the acyl chains, and by substituting the amino acid residues to reduce nephrotoxicity and to improve potency [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. SPR206 is a novel polymyxin B analog for the treatment of gram-negative infection that is undergoing a phase I clinical trial [ 56 ].…”
Section: Discussionmentioning
confidence: 99%